2021
DOI: 10.3390/w13070942
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Phase Composition and Mechanical Properties of Peat Soils Stabilized Using Oil Shale Ash and Pozzolanic Additive

Abstract: Construction of road embankments in peatlands commonly involves replacement of the peat with a fill-up soil of an adequate load-bearing capacity. This usually requires a lowering of the water level, turning a peatland from a carbon sink to a source of greenhouse gases. Thus, alternatives are sought that are less costly in both economic and ecological terms. Mass-stabilization technology can provide a cheap substitute for Portland cement. Calcareous ashes (waste materials), supplemented with pozzolanic and alka… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 18 publications
1
10
0
Order By: Relevance
“…The silicon dioxide reacts with the calcium hydroxide in the presence of water to produce calcium silicate hydrate gel, which is responsible for the strength improvement of problematic soil [ 7 ]. Therefore, SF has been extensively adopted in the stabilization of peat soil [ 7 , 8 , 9 ]. For instance, Kalantari et al [ 7 ] utilized SF in the presence of cement to assess the mechanical and compressibility characteristics of peat.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The silicon dioxide reacts with the calcium hydroxide in the presence of water to produce calcium silicate hydrate gel, which is responsible for the strength improvement of problematic soil [ 7 ]. Therefore, SF has been extensively adopted in the stabilization of peat soil [ 7 , 8 , 9 ]. For instance, Kalantari et al [ 7 ] utilized SF in the presence of cement to assess the mechanical and compressibility characteristics of peat.…”
Section: Introductionmentioning
confidence: 99%
“…The micrographs of untreated and cement-, silica-sand-, and kaolin-stabilized peat reported by Wong et al [ 10 ] revealed a clear transformation from loosely packed peat to a compact solid matrix. Moreover, Rikmann et al [ 9 ] performed microstructural testing (XRD, XRF, and FTIR) of the utilization of cement and shale ash in peat stabilization; their results supported the application of pozzolanic additives such as silica fume, pH-modified alkali, and water glass without the addition of ordinary Portland cement for the stabilization of peat soil. In summation, previous findings have shown that both silica fume and OPC are potential binders in peat stabilization.…”
Section: Introductionmentioning
confidence: 99%
“…Peat soils are defined as highly heterogeneous materials, as they are derived from decomposing organic matter, i.e., plant leaves and roots, and are typically brown or black in color [1]. Peat soil is considered a problematic soil because it has a high natural moisture content and low shear strength [2]. The problems associated with peat soils should be resolved by means of soil stabilization.…”
Section: Introductionmentioning
confidence: 99%
“…Low pH values caused by organic acids (incl. humic and fulvic acids) can prevent the dissolution of clay minerals [3]. Additionally, the effect of humic acids on the setting process of cement is not fully understood.…”
Section: Introductionmentioning
confidence: 99%